How do you think she feels? Vulnerability in empathy and the role of attention in school‐aged children born extremely preterm. (9th June 2015) - Campbell, Catherine; Horlin, Chiara; Reid, Corinne; McMichael, Judy; Forrest, Laura; Brydges, Chris; French, Noel; Anderson, Mike
<x xml:space="preserve">Abstract</x> The aim of this study was to examine empathic competence in children born extremely preterm (EP, <28 weeks) given vulnerabilities in social relationships. Empathy in typically developing children is mediated by executive functions. Executive functioning is also impaired in preterm children. Of particular interest in this study are the attentional components of executive functioning as mediators of empathic development. Thirty‐two 7‐year‐old EP children and 40 age‐matched term children participated in the Project K.I.D.S program and completed the Kids Empathy Development Scale (KEDS), Wechsler Intelligence Scale for Children (WISC‐IV), and Test of Everyday Attention for Children (TEA‐Ch). Children born extremely preterm exhibited poorer performance on all measures. The mediating role of attention in empathy competence was not supported by mediation modelling when FSIQ was controlled. As predicted, the EP group showed weaker empathic development relative to typically developing children. They also showed poorer attentional abilities. However, the effect of preterm birth on empathy was not mediated by executive‐level attention. The cognitive mechanisms underpinning poor empathy competence in EP children remain unclear. Future research needs to examine the role of inhibition, social–emotional recognition, and regulation.